From nucleotides to DNA analysis by a SERS substrate of a self similar chain of silver nanospheres. (23rd October 2015) - Coluccio, M L; Gentile, F; Das, G; Perozziello, G; Malara, N.; Alrasheed, S; Candeloro, P; Fabrizio, E Di
Abstract: In this work we realized a device of silver nanostructures designed so that they have a great ability to sustain the surface-enhanced Raman scattering effect. The nanostructures were silver self-similar chains of three nanospheres, having constant ratios between their diameters and between their reciprocal distances. They were realized by electron beam lithography, to write the pattern, and by silver electroless deposition technique, to fill it with the metal. The obtained device showed the capability to increase the Raman signal coming from the gap between the two smallest nanospheres (whose size is around 10 nm) and so it allows the detection of biomolecules fallen into this hot spot. In particular, oligonucleotides with 6 DNA bases, deposited on these devices with a drop coating method, gave a Raman spectrum characterized by a clear fingerprint coming from the hot spot and, with the help of a fitting method, also oligonucleotides of 9 bases, which are less than 3 nm long, were resolved. In conclusion the silver nanolens results in a SERS device able to measure all the molecules, or part of them, held into the hot spot of the nanolenses, and thus it could be a future instrument with which to analyze DNA portions.